A DREAM CONTENT ANALYSIS: PARRICIDE IN YAGMURCUK KUSU - Beyhan UYGUN AYTEMİZ (Fırat University, 2019)
Kimsecik trilogy, which consists of Yağmurcuk Kuşu, Kale Kapısı and Kanın Sesi, has a special place amongst the works of Yashar Kemal due to the fact that it has traces from the life of the author. Yağmurcuk Kuşu, on the one hand, narrates the migration of Ismail Aga and his family from Van to Çukurova because of war, their settlement in Çukurova, their becoming rich, on the other hand, it focuses on the relationship between İsmail Ağa, his son Mustafa, and his adopted son Salman. How İsmail Ağa is torn between his two “sons” and how Salman and Mustafa become rivals for the love of the father is put up for discussion. It is observed in the text that both Mustafa and his villagers are afraid of Salman, and how Mustafa experiences this fear is examined in detail. Mustafa lives in a nightmarish atmosphere fearing that either his father İsmail Ağa or he himself is to be killed by Salman, and at the end of the novel the father is actually stabbed to death by him. This article examines how parricide is treated in the first book of the trilogy through the analysis of a detailed dream narrative that is revealed at the very beginning of the novel. Mustafa has a dream in which İsmail Ağa is killed by Salman, and the dream consists of several elements taken from the daily life of the child. The dream can be recognized / interpreted as a reflection of Mustafa’s conscious fears of Salman’s existence as a threat to both himself and his father on the one hand, however in the light of Freud’s dream theory the dream gains a symbolic value indicating Mustafa’s oedipus complex.